PENINGKATAN MOTIVASI BELAJAR DAN MANAJEMEN WAKTU UNTUK MENINGKATKAN KUALITAS BELAJAR DAN PRESTASI - Mawarny, Endah; H, Diana Riyana; Amalya, Neneng Tita; Khair, Oki Iqbal; Wardani, Endang Susilo (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
Learning is the main activity in the education process at school. Learning is a conscious effort to change attitudes and behavior. Motivation is needed in an effort to achieve behavioral change. Motivation is one of the factors that drives students to want to learn. Learning motivation can support to be intrinsic motivation (motivations of circumstances that come from within the students themselves that can encourage them to take action to learn) and extrinsic motivation (conditions that come from outside the individual students who encourage them to carry out learning activities). One effort to provide motivation with a more diverse delivery method for students of SMA Muhammadiyah 8 Ciputat with the Motivation Seminar method where the resource persons will help provide material briefings and discussions with students about good and effective learning processes in order to improve quality and achievement. One of reason, we choose SMA Muhammadiyah 8 in Ciputat accordance to contribute growth with the vision, mission and goals of the school.